Epidemiology of adolescent trauma in England: a review of TARN data 2008–2017. Issue 1 (13th November 2019) - Roberts, Zoe; Collins, Julie-Ann; James, David; Bouamra, Omar; Young, Mike; Lyttle, Mark D; Roland, Damian; Mullen, Stephen
Abstract : Objectives: Trauma contributes significantly to adolescent morbidity and mortality. We aimed to ascertain the epidemiology of adolescent trauma to inform prevention strategies. Methods: Data were abstracted from TARN (Trauma Audit Research Network) from English sites over a 10-year period (2008–2017). Adolescents were defined as 10–24 completed years. Descriptive statistical analysis was used in this study. Results: There were 40 680 recorded cases of adolescent trauma. The majority were male (77.3%) and aged 16–24 years old (80.5%). There was a 2.6-fold increase during the study time frame (p<0.0001) in the total annual number of cases reported to TARN. To account for increasing hospital participation, the unit trauma cases per hospital per year was used, noting an increasing trend (p=0.048). Road traffic collision (RTC) was the leading cause of adolescent trauma (50.3%). Pedestrians (41.2%) and cyclists (32.6%) were more prevalent in the 10–15 year group, while drivers (22.9%) and passengers (17.8%) predominated in the 16–24 year group. Intentional injury was reported in 20.7% (alleged assault in 17.2% and suspected self-harm in 3.5%). This was more prevalent in the 16–24 year group. The proportion of trauma reported due to violence has increased with stabbings increasing from 6.9% in 2008 to 10.2% in 2017 (p<0.0001). Evidence of alcohol or drug use was recorded in 20.1% of cases. There was an increase in the number treated in major trauma centres (45.7% 2008 vs 63.5% 2017, p<0.0001). Trauma was more likely to occur between 08:00 and 00:00, at weekends and between April and October. Overall mortality rate was 4.1%. Those with a known psychiatric diagnosis had a higher mortality (6.3% vs 4.4%, p<0.001). Conclusions: RTCs and intentional injuries are leading aetiologies. Healthcare professionals and policy-makers need to prioritise national preventative public health measures and early interventions to reduce the incidence of trauma in this vulnerable age group.